UTILIZATION OF EVALUATION RESULTS IN LEGAL POLICY-MAKING AND ADMINISTRATION - H. Wollmann (Правоприменение)
The article is devoted to the analysis of evaluation method and its impact on legal policy development in governance, including in the area of law enforcement.The author outlines the importance of question whether, when and how the evaluation results of public policies, programs and measures has been utilized (or not utilized) in policy making and policy implementation.In the pursuit of this guiding question the article will come in five steps.First, major variants of evaluation will be briefly presented particularly with an eye on their respective “utilization potential”.Second, different concepts will be sketched that have been forwarded to capture the utilization of social science generated knowledge by political, administrative and social actors. The author outlines a detailed description of types of evaluations: a retrospective, prelimi-nary, ongoing, interactive, – as well as existing concepts of application of its results.Third, looking at Germany, Switzerland and the European Union as “cases in point” perti-ent research findings will be discussed. The article also subjected to a detailed analysis of the experience of Germany, Switzerland and the European Union in the field of utilization of evaluation results.Fourth, a summary and conclusion will be given.Fifth, some remarks on pertinent research needs will be made.The author comes to the conclusion that that the rate of the utilization of evaluation-generated knowledge has so far turned out be, by and large, scarce. The author says that re-garding the politically crucial decisions the political rationality and its underlying political will of the decision-makers prevail while concerning less important decisions evaluation-generated evidence does show some effect and, hence, a dose of scientific rationality comes to the fore.There is also a need for further research on the subject of how should (and should not) use assessment results when making legal and political decisions.